Impurity behaviour in JET-ILW plasmas fuelled with gas and/or with pellets: a comparative study with the transport code COREDIV. (7th May 2021) - Telesca, G.; Ivanova-Stanik, I.; Perez von Thun, Ch.; Aleiferis, S.; Brezinsek, S.; Chomiczewska, A.; Huber, A.; Kowalska-Strzeciwilk, E.; Pawelec, E.; Sertoli, M.; Zagórski, R.; Contributors, JET
Abstract: This study deals with the comparison of impurity behaviour in pellet and gas fuelled JET-ITER like wall pulses with the aim of finding the mechanisms leading to the generally observed higher concentration of tungsten in pellet fuelled plasmas. In fact, tungsten is the main high- Z impurity in the JET-ILW plasmas and is responsible for most of the radiative losses in the plasma core. Analysis of the experimental data pertaining to pulses at different plasma currents, different input power and different electron densities is integrated by numerical modelling with the self-consistent fluid transport code COREDIV. Experimentally, and numerically, the ratio between the radiated power in the divertor and the total one—which results to be an increasing function of the ratio of the electron density at the strike point to the volume average one—is found to be a critical parameter determining impurity accumulation. The higher this value the lower the impurity density in the plasma core. Together with a little higher core impurity residence time, the numerical modelling indicates that the modest divertor screening for the pellet fuelled pulses at low electron flow—characterized by low electron density at the strike point and low perpendicular transport in the SOL—leads to divertor impurity leakage and higher impurity fluxes through the separatrix, in agreement with theory.